2017
DOI: 10.1016/j.tins.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Astrocyte Dysfunction in Parkinson’s Disease Pathogenesis

Abstract: Astrocytes are the most populous glial subtype and are critical for brain function. Despite this, historically there have been few studies into the role that they may have in neurodegenerative diseases, such as Parkinson’s disease (PD). Recently, however, several studies have determined that genes known to have a causative role in the development of PD are expressed in astrocytes and have important roles in astrocyte function. Here, we review these recent developments and discuss their impact on our understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
418
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 485 publications
(435 citation statements)
references
References 99 publications
(147 reference statements)
11
418
0
6
Order By: Relevance
“…[42] Due to its involvement in familial and sporadic PD and the presence of a drugable kinase domain, LRRK2 has become an attractive pharmacological target. [45] Cocultures of various iPSC-derived neural cells will be important to assess cell and noncell autonomous effects. [43] Subsequent investigations also pointed to protein expression levels, focusing on posttranslational modifications such as phosphorylation at serine residues Ser910 and Ser935, located prior to the leucine-rich domain of LRRK2.…”
Section: Discussionmentioning
confidence: 99%
“…[42] Due to its involvement in familial and sporadic PD and the presence of a drugable kinase domain, LRRK2 has become an attractive pharmacological target. [45] Cocultures of various iPSC-derived neural cells will be important to assess cell and noncell autonomous effects. [43] Subsequent investigations also pointed to protein expression levels, focusing on posttranslational modifications such as phosphorylation at serine residues Ser910 and Ser935, located prior to the leucine-rich domain of LRRK2.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, PD is characterized by the deposition of misfolded and ubiquitinated α‐synuclein fibrils in neurons, which are thought to cause neuronal toxicity (Poewe et al, ). Nonfibrillar α‐synuclein accumulation was also observed in the cytoplasm of cortical and subcortical protoplasmic, but not fibrous, astrocytes in PD patients (Booth et al, ; Braak, Sastre, & Del Tredici, ; Song et al, ; Wakabayashi, Hayashi, Yoshimoto, Kudo, & Takahashi, ). Of note, the presence of these inclusions did not correlate with astrogliosis, which was only mild in the SN (Song et al, ).…”
Section: Ipscs Derived Astrocytes As Disease Model: a New Platform Tomentioning
confidence: 99%
“…Less well established, however, is the role that these cells play in disease as both toxic gain of function and LOF have been hypothesized (Liddelow et al, ; Oksanen et al, ). Recently, it was found that genes expressed by human astrocytes are enriched for CNS disease‐linked genes (Booth, Hirst, & Wade‐Martins, ; Kelley, Nakao‐Inoue, Molofsky, & Oldham, ; Zhang et al, ). In particular, single cell RNAseq in human brain revealed that there is an enrichment of genes involved in most neurodegenerative diseases, which are expressed by astrocyte and microglia (Cuevas‐Diaz Duran, Wang, Zheng, Deneen, & Wu, ; Kelley et al, ).…”
Section: Ipscs Derived Astrocytes As Disease Model: a New Platform Tomentioning
confidence: 99%
“…Inflammation involving reactive astrocytes is known to contribute to progression of PD 44 . Involvement of nAChRs in PD was suggested by epidemiological studies showing reduced occurrence of this disease in smokers and altered expression of nAChRs in patients and disease models 4,45 .…”
Section: Ric-3 and Diseases Of The Central Nervous Systemmentioning
confidence: 99%
“…Thus, the mechanisms of action of PD-associated RIC-3 mutations in this disease need to be identified. But, the demonstrated effects of these mutations on α7 nAChR surface expression 40 , the known role of this nAChR in regulating inflammation (above), and contribution of inflammation to neurodegenerative processes occurring in PD 44,50 , suggest a mechanism involving decreased activity of the cholinergic anti-inflammatory pathway as a mechanism explaining effects of both PD-associated RIC-3 mutations and nicotine on PD progression.…”
Section: Ric-3 and Diseases Of The Central Nervous Systemmentioning
confidence: 99%